JENIS TEKNIK DAN BAHAN BAHAN YANG DIGUNAKAN PADA KERAJINAN TANGAN SUMBER BELAJAR SENI BUDAYA DAN PRAKARYA DI SEKOLAH DASAR - Rati Syafiana Putri; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The study aims at describing a variety of handicraft techniques and materials which exist in Sumatera Barat. This study employed qualitative descriptive approach. The subject of this study was handicraft home industry in Sumatera Barat. The data collection of this study obtained by conducting observation, documentation, and interviews. The results indicated that (1) home industry of handicraft in Sumatera Barat is feasible to be utilized as a learning resource in elementary school. In addition, the variety of technique of making handicrafts noted within this study are wickerworking, carving, sewing, tie, stringing-beading, application, embroidering, batik, folding, clay crafting, spinning, rotating, printing, screen printing, painting, scratching and lathing. (2) The variety of handicrafts materials selected or used is in the form of natural and artificial materials such as clay, katu, corn husk, cloth, plastic, and paper.